2019
DOI: 10.1590/2237-6089-2018-0047
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia TreAtment with electRic Transcranial Stimulation (STARTS): design, rationale and objectives of a randomized, double-blinded, sham-controlled trial

Abstract: Introduction Schizophrenia is a severe mental disorder. While some antipsychotic medications have demonstrated efficacy in treating positive symptoms, there is no widely recognized treatment for negative symptoms, which can cause significant distress and impairment for patients with schizophrenia. Here we describe the rationale and design of the STARTS study (Schizophrenia TreAtment with electRic Transcranial Stimulation), a clinical trial aimed to test the efficacy of a non-pharmacological treatment known as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
2
2
0
Order By: Relevance
“…Conversely, in an earlier randomized controlled study [ 43 ], the total cognitive function scores, working memory, and attentional alertness scores of patients treated with tDCS were significantly higher than those in the pseudo-stimulus group. Similarly, previous studies [ 44 , 45 ] have shown that tDCS can improve the patient’s working memory when using the left dorsolateral prefrontal cortex as an anode stimulation point. These results are inconsistent with this research.…”
Section: Discussionsupporting
confidence: 60%
“…Conversely, in an earlier randomized controlled study [ 43 ], the total cognitive function scores, working memory, and attentional alertness scores of patients treated with tDCS were significantly higher than those in the pseudo-stimulus group. Similarly, previous studies [ 44 , 45 ] have shown that tDCS can improve the patient’s working memory when using the left dorsolateral prefrontal cortex as an anode stimulation point. These results are inconsistent with this research.…”
Section: Discussionsupporting
confidence: 60%
“…Conversely, in an earlier randomized controlled study [39] , the total cognitive function scores, working memory, and attentional alertness scores of patients treated with tDCS were signi cantly higher than those in the pseudo-stimulus group. Similarly, previous studies [40,41] have shown that tDCS can improve the patient's working memory ability when using the left dorsolateral prefrontal cortex as an anode stimulation point. These results are inconsistent with this research.…”
Section: Discussionsupporting
confidence: 58%
“…We used opaque, sealed envelopes for allocation concealment. The study protocol was described elsewhere and performed with no significant changes (Supplement 1).…”
Section: Methodsmentioning
confidence: 99%
“…The following stimulation parameters were used: 2 mA; 5 × 7 cm 2 electrodes, with the anode centered over the area corresponding to the left dorsolateral PFC and the cathode centered over the area corresponding to the left temporoparietal junction; and use of the electroencephalography 10–20 system (F3 and T3P3 areas, respectively), with both electrodes’ large axes (7 cm) perpendicular to the skull’s circumference. Computational simulation of the current distribution can be found elsewhere …”
Section: Methodsmentioning
confidence: 99%